Separator and electrochemical device including the same
By using a porous substrate to combine with an inorganic particle layer in the separator, using metal silicate to connect inorganic particles and porous substrates, the problem of reduced mechanical strength and heat resistance of the separator under thin thickness is solved, and a separator with high adhesion and high breathability is achieved, which is suitable for high capacity/high power batteries.
Patent Information
- Application Number
- CN202411269113.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-19
- Filing Date
- 2024-09-11
- Publication Date
- 2025-03-21
AI Technical Summary
The existing diaphragms have problems with reduced mechanical strength and heat resistance at thin thickness, resulting in safety risks in the battery during manufacturing and use.
A separator designed with a porous substrate and an inorganic particle layer is used, wherein the inorganic particle layer consists of inorganic particles, metal silicate inorganic binder and organic compounds with a content smaller than that of inorganic binder. The inorganic particles and porous substrate are connected through metal silicate to form a separator with high adhesion and high breathability.
Even at thin thickness, the diaphragm exhibits excellent heat resistance and adhesion, reducing the risk of the battery ignition or breaking at high temperatures, and achieving thinning of the diaphragm, suitable for high capacity/high power batteries.
Smart Images

Figure CN119674424A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a diaphragm and an electrochemical device comprising the diaphragm. Background Art
[0002] In recent years, with the trend of high capacity and high power of secondary batteries, there is an increasing demand for high strength, high transmittance, thermal stability of the separator and for improving the characteristics of the separator for the electrical safety of the secondary battery during charging and discharging. In the case of separators for lithium secondary batteries, high mechanical strength is required to improve the safety of the battery during manufacturing and use, and high transmittance and high thermal stability are required to increase capacity and power.
[0003] In addition, in order to achieve high capacity and high power characteristics of electrochemical devices, the research trend of the diaphragm is to reduce the thickness of the diaphragm, but when the thickness of the diaphragm becomes thinner, there is a problem of reduced mechanical strength and / or heat resistance. When the mechanical strength and / or heat resistance decreases, the possibility of safety problems occurring during the manufacturing process and use of the battery increases. As an example, a short circuit between the electrodes may occur due to damage or deformation of the diaphragm caused by the temperature rise in the battery, so the risk of overheating or fire of the battery may increase. Summary of the invention
[0004] 1. Technical issues to be resolved
[0005] According to one aspect of the present invention, a separator having excellent heat resistance even in a thin thickness and an electrochemical device including the same can be provided.
[0006] According to another aspect of the present invention, a separator having improved adhesiveness and transmittance even at a thin thickness and an electrochemical device including the same can be provided.
[0007] According to another aspect of the present invention, an electrochemical device having excellent performance can be provided.
[0008] The diaphragm of the present invention can be widely used in electric vehicles, battery charging stations, other green technology fields such as solar power generation and wind power generation using batteries. In addition, the diaphragm of the present invention can be used in eco-friendly electric vehicles and hybrid vehicles to prevent climate change by suppressing air pollution and greenhouse gas emissions.
[0009] (II) Technical solution
[0010] The diaphragm according to the present invention comprises: a porous substrate; and an inorganic particle layer, wherein the inorganic particle layer is located on one side or both sides of the porous substrate, and the inorganic particle layer comprises inorganic particles and an inorganic binder, wherein the inorganic particle layer comprises an organic compound whose content is less than that of the inorganic binder, and the inorganic binder comprises metal silicate.
[0011] In a specific embodiment, the metal silicate may connect and fix the inorganic particles and the inorganic particle layer and the porous substrate.
[0012] In a specific embodiment, the organic compound may include a first organic compound, a second organic compound or a combination thereof, wherein the first organic compound is any one or more selected from polycarboxylates, sulfonates and polysiloxane compounds, and the second organic compound is any one or more selected from ester-based polymers, amide-based polymers, imide-based polymers, acrylic-based polymers, styrene-based polymers, vinyl alcohol-based polymers, vinylpyrrolidone-based polymers, cellulose-based polymers and fluorine-based polymers.
[0013] In a specific embodiment, the organic compound may include less than 30 wt % of the second organic compound, based on the total weight of the organic compound.
[0014] In a specific embodiment, the organic compound may be free of a second organic compound.
[0015] In a specific embodiment, the metal of the metal silicate may be any one or two or more metals selected from Group 1 metals, Group 2 metals and Group 13 metals.
[0016] In a specific embodiment, the metal of the metal silicate may be any one or two or more metals selected from Group 1 metals and Group 2 metals.
[0017] In a specific embodiment, the metal silicate may be represented by the following Chemical Formula 1.
[0018] [Chemical formula 1]
[0019] M 2 O·nSiO 2
[0020] In the chemical formula 1, M is an alkali metal, and n is 4 to 10.
[0021] In a specific embodiment, the inorganic particles may include any one or two or more selected from metal hydroxides, metal oxides, metal nitrides, metal carbides, and metal sulfates.
[0022] In a specific embodiment, the average particle size (D50) of the inorganic particles may be 1 μm or less.
[0023] In a specific embodiment, the total thickness of the inorganic particle layer formed on the porous substrate may be 5 μm or less.
[0024] In a specific embodiment, the thermal shrinkage rate in the width direction of the separator measured after being left at 130° C. for 60 minutes may be 3% or less.
[0025] In a specific embodiment, the thermal shrinkage rate in the width direction of the separator measured after being placed at 150° C. for 60 minutes may be 7% or less.
[0026] In a specific embodiment, the inorganic particle layer may include 0.1 to 20 parts by weight of the metal silicate relative to 100 parts by weight of the inorganic particles.
[0027] In a specific embodiment, the surface of the porous substrate may include polar groups.
[0028] The electrochemical device according to the present invention may include the separator as described above.
[0029] (III) Beneficial effects
[0030] The separator according to the present invention can have excellent heat resistance even at a thin thickness. Therefore, it can have a very low heat shrinkage rate even at a thin thickness.
[0031] Furthermore, the separator according to the present invention can have excellent adhesiveness and transmittance even at a thin thickness.
[0032] Furthermore, the present invention can provide an electrochemical device including the separator according to a specific embodiment, thereby having excellent performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 is a schematic cross-sectional view of a separator according to one embodiment. DETAILED DESCRIPTION
[0034] The present invention is described in detail below, but this is merely exemplary, and the present invention is not limited to the specific embodiments described exemplarily.
[0035] Furthermore, unless otherwise specifically stated, singular forms used in the specification and claims may also include plural forms.
[0036] In addition, the numerical range used in this specification includes the lower limit value and the upper limit value and all values in the range, the increments logically derived under the form and width of the defined range, all values defined therein, and all possible combinations of the upper and lower limits of the numerical range defined in different forms. Unless otherwise specifically defined in this specification, values outside the numerical range that may be generated due to experimental errors or rounding of values are also included in the defined numerical range.
[0037] Furthermore, throughout the specification, unless otherwise specifically stated to the contrary, “comprising” or “including” a certain constituent element means that other constituent elements may also be included or comprised, rather than excluding other constituent elements.
[0038] In this specification, when a layer, film, region, plate or the like is described as being “on” or “over” another part, this includes not only the case of being “directly” “on” another part but also the case where there are other parts in between.
[0039] In this specification, "average particle size" refers to "D50", and "D50" refers to the particle size of inorganic particles corresponding to a cumulative fraction of 50% based on volume. The average particle size can be obtained by sampling the inorganic particles to be measured according to ISO 13320-1 standard and analyzing the particle size distribution results using S3500 of MICROTRAC.
[0040] Figure 1 is a schematic cross-sectional view of a diaphragm according to one embodiment. Figure 1 The present invention provides a diaphragm, which includes: a porous substrate; and an inorganic particle layer, wherein the inorganic particle layer is located on one side or both sides of the porous substrate, and the inorganic particle layer contains inorganic particles and an inorganic adhesive, wherein the inorganic particle layer contains an organic compound whose content is less than that of the inorganic adhesive, and the inorganic adhesive contains metal silicate.
[0041] As a method of ensuring the safety of a battery, a composite separator has been developed in which a porous inorganic particle layer is formed on a porous substrate in the following form, wherein the porous inorganic particle layer contains inorganic particles and a polymer-based organic binder, the inorganic particles are connected to each other through the organic binder, and are bonded to the porous substrate through the organic binder.
[0042] However, in the above-mentioned organic-inorganic composite separator, when a thin inorganic particle layer below a certain thickness is formed, there is a problem that the heat shrinkage rate characteristics at high temperature are reduced. Therefore, it is essentially impossible to achieve a thin film of the separator, and therefore there is a limitation that it is not suitable for high-capacity / high-power batteries.
[0043] In addition, when using an organic adhesive, in order to have sufficient adhesive force, a relatively large amount of organic adhesive above a certain content will be used. Therefore, a chemical reaction occurs between the electrolyte of the battery and the organic adhesive component, which may cause the modification of the adhesive component, or gas is generated due to the reaction, and this gas leaks (leak) due to heat, so there are problems such as reduced battery life. In addition, excessive organic adhesive dissolves in the electrolyte and dissolves out, resulting in reduced electrolyte performance, or due to the electrolyte, the organic adhesive swells, so there are various problems such as the pore layer being closed or the volume of the battery being increased, which reduces battery performance. It has been confirmed that when a thin layer of inorganic particles is formed, the problems caused by the organic adhesive as described above will be further aggravated.
[0044] Therefore, the inventors of the present invention have continued to study to solve the problems of the above-mentioned organic-inorganic composite separator while having excellent heat resistance even at a relatively thin thickness. As a result, it was confirmed that by forming an inorganic particle layer containing an inorganic binder containing a metal silicate and an organic compound whose content is less than that of the inorganic binder, a separator having excellent heat resistance and adhesion even at a thin thickness and excellent transmittance can be provided.
[0045] In a specific embodiment, the metal silicate can connect and fix the inorganic particles and the inorganic particle layer and the porous substrate. It is believed that the diaphragm can show high adhesion because the inorganic particles and / or the inorganic particle layer and the porous substrate are connected or anchored by the metal silicate.
[0046] In the separator according to one embodiment, the inorganic particles may be connected to each other by metal silicate to form pores. That is, the inorganic particle layer may include inorganic particles and an inorganic binder, and the inorganic particle layer may be a porous inorganic particle layer in which the inorganic particles are connected and fixed by the inorganic binder to form pores.
[0047] In a specific embodiment, any one or both of the surface and the hole portion selected from the porous substrate may be coated with a metal silicate. Therefore, the bonding force between the inorganic particle layer and the surface of the porous substrate may also be very excellent. It is believed that this is because the metal silicate not only connects and fixes the inorganic particles to each other, but also penetrates into the inside of the hole formed on the porous substrate and anchors, thus having the effect of firmly fixing to the porous substrate.
[0048] In a specific embodiment, for one or both sides of the porous substrate, the inorganic particle layer can be formed on more than 90% of the total area of each side, specifically more than 95%. More specifically, except for the case where micro defects occur, the inorganic particle layer can be formed on 100% of the total area of each side of the porous substrate, and the inorganic particles of the inorganic particle layer are adjacent to each other and form pores between the inorganic particles.
[0049] In a specific embodiment, the organic compound may refer to an additive used in the manufacture of a diaphragm known in the art. As an example of the additive, an organic compound comprising an organic binder, a dispersant, a wetting agent, a slip agent, a defoamer or a thickener may be cited. Specifically, the organic compound may include any one or more of a dispersant selected from a coating slurry used to prevent the aggregation of inorganic particles in the inorganic particle layer, a wetting agent to improve the coating property of the slurry, and an organic binder to improve the adhesion between inorganic particles and / or between the inorganic particle layer and the porous substrate.
[0050] In the case of a separator according to a specific embodiment, since an inorganic binder containing metal silicate is used and an organic compound containing an organic binder in a significantly smaller amount than in the past, an excellent thermal shrinkage property under a thin thickness that cannot be achieved by a separator using an excessive amount of an organic compound containing an organic binder can be achieved. Therefore, it is possible to prevent fire or rupture caused by abnormal phenomena such as a sharp rise in temperature, and to achieve a thin film of a secondary battery separator, so it is suitable for application in high-capacity / high-power batteries. In addition, in the case of a separator according to a specific embodiment, the bonding force between the particles contained in the inorganic particle layer and the bonding force between the porous substrate and the inorganic particle layer are excellent.
[0051] As for the separator according to a specific embodiment, since the inorganic particle layer contains metal silicate as an inorganic binder, problems such as pore clogging and expansion caused by organic compounds such as polymer-based organic binders do not occur, and the ion migration is very excellent, so there is no obstacle to the migration of lithium ions and other ions, and the electrical characteristics such as the capacity or efficiency of the battery can be significantly improved.
[0052] In a specific embodiment, the organic compound may include a first organic compound, a second organic compound or a combination thereof, wherein the first organic compound is any one or more selected from polycarboxylates, sulfonates and polysiloxane compounds, and the second organic compound is any one or more selected from ester-based polymers, amide-based polymers, imide-based polymers, acrylic-based polymers, styrene-based polymers, vinyl alcohol-based polymers, vinylpyrrolidone-based polymers, cellulose-based polymers and fluorine-based polymers. However, the organic compounds may be replaced by other constituent elements as long as they do not exceed the scope of the present invention.
[0053] In a specific embodiment, the first organic compound may be an additive other than the binder. At this time, the additive other than the binder may be any one or more of a dispersant, a wetting agent, a slip agent, a defoamer, and a thickener, and is not limited thereto, and may be an additive that can be generally included in the inorganic particle layer. In addition, the dispersant may prevent the aggregation of inorganic particles in the coating slurry used when forming the inorganic particle layer, and the wetting agent may improve the coating property of the slurry.
[0054] In a specific embodiment, the second organic compound may be an organic binder, and the organic binder may connect and fix the inorganic particles and the inorganic particle layer and the porous substrate.
[0055] In a non-limiting manner, the polycarboxylate may be any one or more selected from sodium polyacrylate, ammonium polyacrylate, etc. In a non-limiting manner, the sulfonate may be any one or more selected from dialkyl sulfosuccinates, alkyl diphenyl oxide disulfonates, alkyl benzene sulfonates, etc. The polysiloxane compound may be any one or more selected from 3-(polyethylene)propyl heptamethyltrisiloxane, 3-(3-hydroxypropyl)-heptamethyltrisiloxane ethoxylated acetate, methyl(propyl hydroxide)(ethoxylated)bis(triethylsiloxy)silane, etc.
[0056] The ester-based polymer may be any one or more selected from polyethylene terephthalate, polyethylene naphthalate (PEN), etc. The amide-based polymer may be any one or more selected from polyamide-6, polyamide-66, etc. The imide-based polymer may be any one or more selected from polyimide, polyetherimide, polyesterimide, etc. The acrylic-based polymer may be any one or more selected from polyacrylamide, polymethacrylate, polyethyl acrylate, polyacrylate, polybutyl acrylate, acrylic-methacrylic acid copolymer, etc. The styrene-based polymer may be any one or more selected from polystyrene, poly-α-methylstyrene, polybrominated styrene, etc. The vinyl alcohol-based polymer may be any one or more selected from polyvinyl alcohol, polyvinyl acetate, polyvinyl acetate-polyvinyl alcohol copolymer, etc. The vinyl pyrrolidone-based polymer may be any one or more selected from polyvinyl pyrrolidone and copolymers containing vinyl pyrrolidone, etc. In addition, the cellulose-based polymer may be any one or more selected from carboxymethyl cellulose, cellulose acetate propionate, cellulose acetate, cellulose acetate butyrate, etc. The fluorine-based polymer may be any one or more selected from polyvinylidene fluoride, polytetrafluoroethylene, polyhexafluoropropylene, polyvinylidene fluoride-hexafluoropropylene, polychlorotrifluoroethylene, and the like.
[0057] In a specific embodiment, the organic compound may contain less than 30% by weight of the second organic compound, specifically, less than 20% by weight, less than 10% by weight, or less than 5% by weight of the second organic compound, based on the total weight of the organic compound. When the second organic compound in the above range is contained, a separator can be provided, in which problems such as pore clogging and expansion caused by the second organic compound do not occur, and ion migration is very excellent, so there is no obstacle in the migration of lithium ions and other ions, and the electrical characteristics such as the capacity or efficiency of the battery are significantly improved.
[0058] In a specific embodiment, the organic compound may not contain a second organic compound. Since the separator according to a specific embodiment contains metal silicate as an inorganic binder, even if it does not contain a second organic compound that can serve as an organic binder, it can have excellent heat resistance and adhesion at a thin thickness while more effectively suppressing the problem of reduced battery performance.
[0059] In a specific embodiment, the content of the organic compound is not particularly limited as long as it is less than the content of the inorganic binder. For example, the inorganic particle layer may contain 0.001-15 parts by weight, 0.001-13 parts by weight, or 0.001-8 parts by weight of the organic compound relative to 100 parts by weight of the inorganic particles. More specifically, the content of the organic compound may be 0.001-5 parts by weight, 0.01-3 parts by weight, 0.1-2 parts by weight, or 0.1-1 parts by weight relative to 100 parts by weight of the inorganic particles.
[0060] In a specific embodiment, the metal of the metal silicate may be any one or more metals selected from Group 1 metals, Group 2 metals and Group 13 metals. That is, the metal may be one or more selected from lithium (Li), sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), aluminum (Al), gallium (Ga) and indium (In).
[0061] In a specific embodiment, in terms of improving the heat resistance and adhesion of the diaphragm, the metal of the metal silicate may preferably be any one or more metals selected from Group 1 metals and Group 2 metals. That is, the metal may be one or more selected from lithium (Li), sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr) and barium (Ba). More preferably, the metal of the metal silicate may be one or more alkali metals selected from lithium (Li), sodium (Na), potassium (K), rubidium (Rb) and cesium (Cs). In the case of the alkali metal silicate, the thermal shrinkage rate is the lowest compared to other types of metals, thereby achieving the most excellent heat resistance.
[0062] In a specific embodiment, the metal silicate may have a structure containing metal oxide and silicon dioxide in a certain molar ratio. Specifically, the molar ratio of metal oxide to silicon dioxide may be 1:4 to 1:10, specifically 1:4 to 1:9, more specifically 1:4.5 to 1:8.5, and further specifically 1:5 to 1:8.
[0063] In a specific embodiment, the metal silicate may be represented by the following Chemical Formula 1.
[0064] [Chemical formula 1]
[0065] M 2 O·nSiO 2
[0066] In the chemical formula 1, M is an alkali metal, and n is 4 to 10.
[0067] Since the metal silicate satisfies the chemical formula 1, the effect of connecting and fixing the inorganic particles and the inorganic particle layer and the porous substrate can be better achieved. Therefore, in the case of a separator according to a specific embodiment, not only the bonding force between the inorganic particles and the bonding force between the porous substrate and the inorganic particle layer are more excellent, but also excellent thermal shrinkage characteristics can be achieved at a thin thickness.
[0068] In the Chemical Formula 1, n may be 4 to 9, 4.5 to 8.5, or 5 to 8.
[0069] In a specific embodiment, the inorganic particles are not limited as long as they are inorganic particles used in the art. As a non-limiting example, the inorganic particles may include any one or more selected from metal hydroxides, metal oxides, metal nitrides, metal carbides, and metal sulfates. For example, the inorganic particles may include magnesium oxide (MgO), magnesium hydroxide (Mg(OH) 2 ), aluminum oxide (Al2 O 3 ), boehmite (γ-AlO(OH)), aluminum hydroxide (Al(OH) 3 ), silicon dioxide (SiO 2 ), silicon carbide (SiC), calcium oxide (CaO), titanium dioxide (TiO 2 ), SrTiO 3 ), barium titanate (BaTiO 3 ), barium sulfate (BaSO 4 )、ZnO、Yttrium Oxide (Y 2 O 3 )、ZrO 2 ), tin oxide (SnO 2 ) and cerium oxide (CeO 2 In terms of battery stability, the inorganic particles may be selected from bohemite, aluminum hydroxide (Al(OH) 3 ) and magnesium hydroxide (Mg(OH) 2 ) or any one or more metal hydroxide particles.
[0070] In a specific embodiment, the morphology of the inorganic particles is not limited, and may be spherical, elliptical, needle-shaped, or the like.
[0071] In a specific embodiment, the average particle size (D50) of the inorganic particles can be less than 1 μm, less than 0.7 μm, more than 0.01 μm, more than 0.05 μm, or a value between the above values, specifically 0.01-1 μm or 0.05-0.7 μm. When the average particle size of the inorganic particles meets the above range, a more excellent thermal shrinkage property can be achieved at a thin thickness.
[0072] Preferably, the average particle size (D50) of the inorganic particles can be less than 0.5 μm, specifically less than 0.35 μm. According to a specific embodiment, the diaphragm contains metal silicate and inorganic particles having an average particle size (D50) of less than 0.5 μm or less than 0.35 μm, thereby further improving the thermal shrinkage characteristics under thin thickness.
[0073] In a specific embodiment, the inorganic particle layer may be coated on one or both sides of the porous substrate. When the inorganic particle layer is coated on both sides of the porous substrate, the thickness of the inorganic particle layer coated on one side and the other side may be the same or different.
[0074] In a specific embodiment, the total thickness of the inorganic particle layer formed on the porous substrate can be 5 μm or less, 3 μm or less, 2.5 μm or less, 2 μm or less, 0.1 μm or more, 0.5 μm or more, 1 μm or more, or a value between the above values. Specifically, the total thickness of the inorganic particle layer can be 0.1-5 μm, 0.5-3 μm, 1-2.5 μm, or 1-2 μm. However, this means that significantly improved heat resistance and adhesion can be achieved even at the thickness in the above range, so it is not necessarily limited thereto, and the total thickness of the inorganic particle layer can be changed as long as it does not exceed the scope of the present invention.
[0075] The separator according to one embodiment may have excellent heat resistance even at a thin thickness. In one embodiment, the thermal shrinkage in the width direction measured after the separator is placed at 130° C. for 60 minutes may be 3% or less, preferably 2% or less, and more preferably 1% or less.
[0076] In addition, the separator according to a specific embodiment may have excellent heat shrinkage characteristics at higher temperatures. In a specific embodiment, the heat shrinkage in the width direction of the separator measured after being placed at 150° C. for 60 minutes may be 7% or less, preferably 5% or less, and more preferably 3% or less.
[0077] With regard to the Gurley permeability of the diaphragm according to a specific embodiment measured according to ASTM D726, the ΔGurley permeability calculated by the following calculation formula 1 can be 50 seconds / 100 milliliters (sec / 100cc) or less, specifically 40 seconds / 100 milliliters or less. As an example, the lower limit of the Gurley permeability can be 5 seconds / 100 milliliters.
[0078] [Calculation formula 1]
[0079] ΔGurley air permeability (seconds / 100 ml) = Gurley air permeability of the diaphragm formed with the inorganic particle layer - Gurley air permeability of the porous substrate
[0080] In a specific embodiment, the inorganic particle layer may include 0.1-20 parts by weight of the metal silicate, and may include 1-15 parts by weight or 1-10 parts by weight of the metal silicate relative to 100 parts by weight of the inorganic particles, but is not necessarily limited thereto.
[0081] In a specific embodiment, the surface of the porous substrate may contain polar groups. In this case, the polar groups may be, for example, carboxylic acid groups, aldehyde groups, or hydroxyl groups, but are not limited thereto. Since the separator according to a specific embodiment includes a porous substrate having a surface containing polar groups, excellent thermal shrinkage characteristics and adhesion at a thin thickness can be achieved at the same time.
[0082] The polar group may be introduced by a specific surface treatment. Specifically, the surface treatment is not limited in its method, but may be plasma treatment, corona discharge treatment or electron beam treatment in the presence of one or more selected from oxygen, air and ozone.
[0083] In a specific embodiment, the porous substrate may use various porous polymer films, sheets, nonwoven fabrics, woven fabrics, etc. made of polymers used as separators, and may also include a porous substrate having a laminated structure in which the layers are laminated into two or more layers.
[0084] In a specific embodiment, the porous substrate may be a polyolefin-based porous substrate such as polyethylene, polypropylene, or copolymers thereof, but is not limited thereto, and all porous substrates known as porous substrates for separators of electrochemical devices may be used.
[0085] In a specific embodiment, the porosity of the porous substrate may be 20-60%, specifically 30-60%, but is not limited thereto. The porosity may be calculated by the following formula.
[0086] Porosity (%) = (1 – true density / bulk density) × 100
[0087] True density (g / cm 3 ) = CCS mass (g) / CCS volume (cm 3 )
[0088] * Volume (cm 3 ) = CCS thickness (cm) × CCS area (cm 2 );
[0089] CCS = ceramic coated diaphragm (porous ceramic + porous PE)
[0090] Bulk density (g / cm 3 ) = ρ 陶瓷 ×(m 陶瓷 / m 复合物 )+ρ PE ×(m PE / m 复合物 )
[0091] *ρ = theoretical density of bulk material;
[0092] Composite (non-porous ceramic + non-porous PE)
[0093] In a specific embodiment, the thickness of the porous substrate may be 1-25 μm, 3-20 μm or 5-15 μm, but is not necessarily limited thereto. The thickness may be measured using a Mitutoyo Thickness Gauge.
[0094] In a specific embodiment, the average thickness of the separator may be 5-30 μm, 10-25 μm or 10-20 μm, but is not necessarily limited thereto. The average thickness may be measured by the following method. Specifically, the separator may be stacked into 10 layers, and the thickness may be measured using a Mitutoyo thickness gauge. Then, the thickness may be divided by 10 to obtain the thickness of a single layer. Then, the same steps may be repeated for 5 points in the TD direction, and the average value may be calculated.
[0095] In a specific embodiment, the inorganic particle layer includes an organic compound whose content is less than that of the inorganic binder, which means that it also includes a case where no organic compound is contained. That is, the inorganic particle layer can be composed of inorganic particles and metal silicate inorganic binder. The inorganic particle layer as described above can be bonded to the porous substrate with very excellent bonding force even in the absence of the above-mentioned organic compound, thereby ensuring the stability of the battery and achieving excellent thermal shrinkage characteristics at a thin thickness that cannot be achieved by a separator using an organic compound such as an excessive amount of an organic binder.
[0096] Hereinafter, the method for producing the separator of the present invention will be described.
[0097] The method for manufacturing the separator of the present invention may include the following steps: preparing a coating slurry containing inorganic particles and metal silicate; and coating the coating slurry on one or both sides of a porous substrate and drying the coating slurry to form an inorganic particle layer.
[0098] The description of the porous substrate, the inorganic particle layer, the inorganic particles, and the metal silicate is the same as described above, and thus a detailed description is omitted.
[0099] The method for preparing the coating slurry can apply conventional methods known in the technical field without limitation. Although not particularly limited, according to non-limiting examples, inorganic particles can be dispersed by stirring to prepare the slurry, and aggregated inorganic particles can also be dispersed by using a ball mill, a bead mill, etc.
[0100] The coating slurry may include inorganic particles, an inorganic binder and a solvent. The solvent may be water, ethanol, methanol, propanol and other lower alcohols, dimethylformamide, acetone, tetrahydrofuran, diethyl ether, dichloromethane, N-methyl-2-pyrrolidone, hexane, cyclohexane and other solvents or mixtures thereof, but is not necessarily limited thereto.
[0101] In a specific embodiment, the solid content of the coating slurry is not particularly limited, but can be, for example, 1-50% by weight, 5-30% by weight, 10-30% by weight, but is not limited thereto.
[0102] In a specific embodiment, the coating slurry may further include an organic compound whose content is less than that of the inorganic binder. The description of the organic compound is the same as above, so the detailed description is omitted.
[0103] In a specific embodiment, the metal silicate contained in the coating slurry may have a structure containing metal oxide and silicon dioxide in a certain molar ratio, and in terms of the coating property of the coating slurry, may contain metal oxide, silicon dioxide and water in a certain molar ratio. Specifically, the molar ratio of metal oxide to silicon dioxide may be 1:4 to 1:10, specifically 1:4 to 1:9, more specifically 1:4.5 to 1:8.5, and further specifically 1:5 to 1:8.
[0104] In a specific embodiment, the metal silicate included in the coating slurry may be represented by the following Chemical Formula 1 or Chemical Formula 2.
[0105] [Chemical formula 1]
[0106] M 2 O·nSiO 2
[0107] In the chemical formula 1, M is an alkali metal, and n is 4 to 10.
[0108] [Chemical formula 2]
[0109] M 2 O·nSiO 2 ·xH 2 O
[0110] In the chemical formula 2, M is an alkali metal, n is 4 to 10, and x is an integer of 50 to 150.
[0111] In the Chemical Formula 1 or Chemical Formula 2, n may be 4 to 9, 4.5 to 8.5, or 5 to 8.
[0112] Since the metal silicate satisfies the chemical formula 1 or the chemical formula 2, the effect of connecting and fixing the inorganic particles and the inorganic particle layer and the porous substrate can be better achieved. Therefore, in the case of a separator according to a specific embodiment, not only the bonding force between the inorganic particles and the bonding force between the porous substrate and the inorganic particle layer are more excellent, but also excellent thermal shrinkage characteristics can be achieved at a thin thickness.
[0113] In the manufacturing method of the diaphragm according to a specific embodiment, before the step of forming the inorganic particle layer, a step of introducing polar groups on the surface of the porous substrate by hydrophilic surface treatment may be further included. At this time, the polar group may be, for example, a carboxylic acid group, an aldehyde group or a hydroxyl group, but is not limited thereto. In a specific embodiment, the hydrophilic surface treatment may be carried out by including one or more of corona discharge treatment and plasma discharge treatment. Due to the introduction of polar groups on the surface of the porous substrate, a diaphragm having excellent thermal shrinkage characteristics and adhesion at the same time can be manufactured at a thin thickness.
[0114] The method for applying the coating slurry can use conventional methods known in the art without limitation, and according to non-limiting examples, roller coating, spin coating, dip coating, rod coating, die coating, slit coating, inkjet printing, and methods combining them can be used. The coated slurry can be formed into an inorganic particle layer by drying. The drying for forming the inorganic particle layer is not particularly limited, but can be dried at less than 100° C. or at 30-60° C.
[0115] The present invention can provide an electrochemical device, the electrochemical device comprising a diaphragm according to one of the above-mentioned specific embodiments. Since the electrochemical device comprises the diaphragm as described above, it can have excellent thermal stability at high temperatures. In addition, since the electrochemical device comprises the diaphragm as described above, the resistance is reduced, so it can have significantly excellent life characteristics.
[0116] The electrochemical device may be any known energy storage device and is not particularly limited, but as a non-limiting example, a lithium secondary battery may be cited. The lithium secondary battery is well known and its structure is also known, so it is not specifically described in the present invention.
[0117] A lithium secondary battery according to one embodiment may include the separator between a positive electrode and a negative electrode. At this time, the positive electrode and the negative electrode may be used without limitation as long as they are generally used for lithium secondary batteries.
[0118] Generally, when the separator according to a specific embodiment is used for a battery, a conventional manufacturing method is followed, that is, by providing a negative electrode, a separator and a positive electrode, assembling them and injecting an electrolyte, so it will not be described in detail here.
[0119] The embodiments of the present invention are further described below with reference to specific experimental examples. The embodiments and comparative examples included in the experimental examples are only used to illustrate the present invention and are not used to limit the claims. Various modifications and variations can be made to the embodiments within the scope of the present invention and the technical concept, which is obvious to those skilled in the art, and it is natural that such modifications and variations belong to the scope of the claims.
[0120] [Measurement methods of physical properties]
[0121] 1. Measurement of thermal shrinkage (%)
[0122] Cut the membrane into a square shape with a side length of 10 cm, and mark the width direction (transverse direction, TD) and machine direction (machine direction, MD). Place the sample in the middle, put 5 pieces of paper on the top and bottom of the sample, and wrap the four sides of the paper with tape. Place the paper-wrapped sample in a hot air drying oven at 130°C (or 150°C) for 60 minutes. After that, take out the sample, measure the membrane with a camera, and then calculate the thermal shrinkage in the width direction using the following formula.
[0123] TD heat shrinkage rate (%) = ((TD length before heating - TD length after heating) / TD length before heating) × 100
[0124] 2. Measurement of ΔGurley air permeability (seconds / 100 ml)
[0125] Δ Gurley air permeability is measured using a Densometer from Toyoseiki Co., Ltd. in accordance with ASTM D726. Gurley air permeability is measured by recording the time required for 100 ml of air to pass through a membrane with an area of 1 square inch in seconds, and then calculated using the following formula.
[0126] ΔGurley air permeability (seconds / 100 ml) = Gurley air permeability of the diaphragm formed with the inorganic particle layer - Gurley air permeability of the porous substrate
[0127] 3. Cardboard Adhesion Test
[0128] The diaphragm was cut into a size of 50 mm in width × 50 mm in length and placed on the rubber mat with the inorganic particle layer facing downward. A black cardboard (20 mm in width × 50 mm in length × 0.25 mm in thickness) was placed between the diaphragm and the rubber mat and a certain pressure (10 g / cm 2). The black cardboard was forcibly removed from the side and the degree of inorganic matter adhering to the surface was confirmed. According to the degree of adhesion, it was judged as A / B / C according to the following grade.
[0129] A: No adhesion
[0130] B: A small amount of inorganic matter adheres
[0131] C: The level of adhesion of adhesive and inorganic materials together
[0132] 4. Measurement of battery electrical characteristics
[0133] Batteries were manufactured using the separators of the following examples and comparative examples as follows. The manufactured batteries were fully charged to 4.2 V after aging and degassing, and the initial resistance (mΩ) of the batteries was measured by J-pulse method.
[0134] Based on the total weight of the positive electrode active material, 94 wt% of LiCoO 2 , 2.5 wt % of polyvinylidene fluoride as a binder, and 3.5 wt % of carbon black as a conductive agent are added to N-methyl-2-pyrrolidone (NMP) as a solvent and stirred to prepare a uniform positive electrode slurry. The prepared slurry is coated on an aluminum foil with a thickness of 30 μm and dried and rolled to manufacture a positive electrode with a total thickness of 150 μm. Based on the total weight of the negative electrode active material, 95 wt % of artificial graphite, 3 wt % of acrylic latex with a Tg of -52°C as a binder, and 2 wt % of carboxymethyl cellulose (CMC) as a thickener are added to water as a solvent and stirred to prepare a uniform negative electrode slurry. The prepared slurry was coated on a copper foil with a thickness of 20 μm and dried and rolled to produce a negative electrode with a total thickness of 150 μm. The prepared positive electrode, negative electrode and separators of the embodiments and comparative examples were used, and a soft-pack type battery was assembled by stacking the separator between the positive electrode and the negative electrode, and then 1M lithium hexafluorophosphate (LiPF) was dissolved in a solution containing ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) in a volume ratio of 30:50:20. 6 ) of the electrolyte and then sealed to manufacture a secondary battery with a capacity of 2Ah.
[0135] <Example 1>
[0136] Preparation of coating slurry
[0137] Based on the total weight of the solid matter, 100 parts by weight of boehmite as inorganic particles having an average particle size (D50) of 0.2 μm and 1.5 parts by weight of polycarboxylate (HS-DISPERSANT 5803 from San Nopco) as a dispersant were added to distilled water and dispersed for 10 minutes using a bead mill to prepare a mixture. Next, 5 parts by weight of lithium silicate (Li 2 O·nSiO 2 , n=5) and 0.2 parts by weight of dioctyl sodium sulfosuccinate as a wetting agent were mixed and stirred to prepare a coating slurry with a solid concentration of 20% by weight.
[0138] Diaphragm manufacturing
[0139] As a porous substrate, a polyethylene porous film (porosity: 42%, average thickness: 9 μm) with polar groups introduced on the surface was used. The two sides of the porous film were subjected to corona discharge treatment (power density of 2 W / mm) to introduce polar groups on the surface, and the speed of the corona surface treatment was set to 5 meters per minute (mpm). The obtained coating slurry was applied on both sides of the porous substrate by bar coating and then dried, thereby manufacturing a diaphragm with an inorganic particle layer having an average thickness of 1.0 μm formed on both sides of the porous substrate. The physical properties of the diaphragm are recorded in Table 1 below.
[0140] <Example 2>
[0141] The separator was manufactured in the same manner as in Example 1, except that the contents of the dispersant and the wetting agent were changed to 0.7 parts by weight and 0.05 parts by weight, respectively, and used when preparing the coating slurry. The physical properties of the separator are described in Table 1 below.
[0142] <Example 3>
[0143] The separator was manufactured in the same manner as in Example 1, except that sodium silicate (Na 2 O·nSiO 2 , n=5) to replace lithium silicate. The physical properties of the separator are recorded in the following Table 1.
[0144] <Example 4>
[0145] The separator was manufactured in the same manner as in Example 1, except that potassium silicate (K 2 O·nSiO2 , n=5) to replace lithium silicate. The physical properties of the separator are recorded in the following Table 1.
[0146] <Example 5>
[0147] The separator was manufactured in the same manner as in Example 1, except that aluminum silicate (Al 2 O 3 nSiO 2 , n=5) to replace lithium silicate. The physical properties of the separator are recorded in the following Table 1.
[0148] <Example 6>
[0149] The separator was manufactured in the same manner as in Example 1 except that boehmite having an average particle size (D50) of 0.6 μm was used as the inorganic particles instead of boehmite having an average particle size (D50) of 0.2 μm. The physical properties of the separator are shown in Table 1 below.
[0150] <Example 7>
[0151] The separator was manufactured in the same manner as in Example 1, except that lithium silicate (Li 2 O·nSiO 2 ) to replace lithium silicate (Li 2 O·nSiO 2 ). The physical properties of the diaphragm are shown in Table 1 below.
[0152] <Example 8>
[0153] The separator was manufactured in the same manner as in Example 1, except that lithium silicate (Li 2 O·nSiO 2 ) to replace lithium silicate (Li 2 O·nSiO 2 ). The physical properties of the diaphragm are shown in Table 1 below.
[0154] <Example 9>
[0155] The separator was manufactured in the same manner as in Example 1, except that lithium silicate (Li 2 O·nSiO 2 ) to replace lithium silicate (Li 2 O·nSiO 2 ). The physical properties of the diaphragm are shown in Table 1 below.
[0156] <Example 10>
[0157] The separator was manufactured in the same manner as in Example 1, except that a polyethylene porous film (porosity: 42%, average thickness: 9 μm) without corona discharge treatment and without polar groups introduced on the surface was used as the porous substrate. The physical properties of the separator are shown in Table 1 below.
[0158] <Comparative Example 1>
[0159] The separator was manufactured in the same manner as in Example 1, except that 3 parts by weight of a glass transition temperature (T g ) was used to replace the lithium silicate with acrylic latex having a temperature of -52°C. The physical properties of the separator are shown in Table 1 below.
[0160] <Comparative Example 2>
[0161] The separator was manufactured in the same manner as in Example 1, except that 3 parts by weight of a polyacrylamide-based polymer (weight average molecular weight: 300,000 g / mol) was used as a binder instead of lithium silicate relative to 100 parts by weight of the inorganic particles. The physical properties of the separator are shown in Table 1 below.
[0162] <Comparative Example 3>
[0163] The separator was manufactured in the same manner as in Example 1, except that 3 parts by weight of lithium silicate (Li 2 O·nSiO 2 , n=5) and 2 parts by weight of glass transition temperature (T g ) is an acrylic latex at -52° C. The physical properties of the separator are shown in Table 1 below.
[0164] [Table 1]
[0165]
[0166] Referring to Table 1, in the diaphragms of Examples 1 to 10, it was confirmed that compared with the diaphragm of the comparative example, even at a thin thickness, the heat shrinkage rate at 130°C was less than 1%, and the heat shrinkage rate at 150°C was less than 7%, so the heat resistance was excellent, and there was no adhesion or a small amount of adhesion in the adhesion test, so the adhesion was also excellent.
[0167] On the other hand, in the separator of Comparative Example 1, since a granular organic polymer is used as a binder, it is confirmed that the heat resistance and the adhesive force are significantly reduced at a thin thickness. In the separator of Comparative Example 2, since a water-soluble organic polymer is used as a binder, it is confirmed that the heat resistance is reduced at a thin thickness compared with the example.
[0168] In addition, in the diaphragm of Comparative Example 3, although the metal silicate according to a specific embodiment of the present invention is included as an inorganic binder, since the total content of organic compounds including dispersants, wetting agents and organic binders is greater than the content of the inorganic binder, it is confirmed that the heat resistance and adhesion are reduced at a thin thickness compared with the examples.
[0169] As described above, it can be seen that the inorganic particle layer of the separator of the present invention contains metal silicate as an inorganic binder and contains an organic compound in a smaller content than the inorganic binder, and thus can simultaneously achieve remarkably excellent heat resistance, air permeability, and adhesiveness.
[0170] The above-described contents are merely examples of applying the principles of the present invention, and other configurations may be included without departing from the scope of the present invention.
Claims
1. A diaphragm, comprising: Porous substrates; and an inorganic particle layer, the inorganic particle layer being located on one side or both sides of the porous substrate and comprising inorganic particles and an inorganic binder, The inorganic particle layer includes an organic compound whose content is less than that of the inorganic binder, and the inorganic binder includes metal silicate.
2. The diaphragm according to claim 1, wherein The metal silicate connects and fixes the inorganic particles and the inorganic particle layer and the porous substrate.
3. The diaphragm according to claim 1, wherein The organic compound includes a first organic compound, a second organic compound or a combination thereof, wherein the first organic compound is any one or more selected from polycarboxylates, sulfonates and polysiloxane compounds, and the second organic compound is any one or more selected from ester-based polymers, amide-based polymers, imide-based polymers, acrylic-based polymers, styrene-based polymers, vinyl alcohol-based polymers, vinylpyrrolidone-based polymers, cellulose-based polymers and fluorine-based polymers.
4. The diaphragm according to claim 3, wherein: The organic compound includes less than 30 wt % of the second organic compound based on the total weight of the organic compound.
5. The diaphragm according to claim 4, wherein The organic compound does not contain a second organic compound.
6. The diaphragm according to claim 1, wherein The metal of the metal silicate is any one or two or more metals selected from Group 1 metals, Group 2 metals and Group 13 metals.
7. The diaphragm according to claim 1, wherein The metal of the metal silicate is any one or two or more metals selected from Group 1 metals and Group 2 metals.
8. The diaphragm according to claim 7, wherein: The metal silicate is represented by the following chemical formula 1: [Chemical formula 1] M2O·nSiO2 In the chemical formula 1, M is an alkali metal, and n is 4 to 10.
9. The diaphragm according to claim 1, wherein: The inorganic particles include any one or two or more selected from the group consisting of metal hydroxides, metal oxides, metal nitrides, metal carbides, and metal sulfates.
10. The diaphragm according to claim 1, wherein The average particle size D50 of the inorganic particles is less than 1 μm.
11. The diaphragm according to claim 1, wherein The total thickness of the inorganic particle layer formed on the porous substrate is 5 μm or less.
12. The diaphragm according to claim 1, wherein The heat shrinkage rate in the width direction of the separator measured after leaving it at 130° C. for 60 minutes was 3% or less.
13. The diaphragm according to claim 1, wherein The heat shrinkage rate in the width direction of the separator measured after leaving it at 150° C. for 60 minutes was 7% or less.
14. The diaphragm according to claim 1, wherein The inorganic particle layer includes 0.1 to 20 parts by weight of the metal silicate relative to 100 parts by weight of the inorganic particles.
15. The diaphragm according to claim 1, wherein The surface of the porous substrate includes polar groups. 16 . An electrochemical device comprising the separator according to claim 1 .
Citation Information
Cited By
Separator and preparation method therefor, and electrochemical device
WO2026114317A1